Application of Globally Harmonized System of Classification and Labeling of Chemicals (GHS) in Chemical Management of an Automotive Parts Manufacture - Soontornchai, Sarisak; Sairam, Wanvisa (Thai Journal of Toxicology, 2020)
The objectives of this quasi-experimental research were: (1) to explore the problems of chemicals management in an automotive parts manufacturer; (2) to classify and communicate hazards of flammable chemicals according to Globally Harmonized System of Classification and Labeling of Chemicals (GHS); and (3) to compare knowledge and practice on handling of flammable chemicals of the studied manufacture’s workers before and after implementing GHS. The studied samples selected by purposive sampling consisted of: (1) flammable chemicals including LPG, spraying color, methyl ethyl ketone (MEK) and primer; and (2) a total of 130 workers in production and warehouse section working with flammable chemicals. The instruments used were interviewing form, chemical knowledge test before and after training, and survey form of correct practice in chemical management. Reliability value of the knowledge test was 0.6232. The data were analyzed by frequency distribution, percentage, mean, standard deviation, and t-test. The findings of this study were that : (1) the employees had chemical knowledge and information acquisition of flammable chemicals at the low level; (2) all chemicals were physical hazard as flammable chemical with acute oral toxicity and specific target organ toxicity of nervous system; and (3) average scores of the knowledge on hazard communication of chemicals according to GHS (2.390) and proper practice with these chemicals (2.920) were higher than those of before training (1.690 and 1.330) (p<0.001). In conclusion, the workers had more chemical management improvement.